PERAN ILO (INTERNATIONAL LABOUR ORGANIZATION) DALAM MENANGANI KECELAKAAN KERJA PADA INDUSTRI GARMEN DI BANGLADESH STUDI KASUS TRAGEDI RANA PLAZA TAHUN 2013 - Harry Panduari Tambun; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to determine the role of International Labour Organization (ILO) in dealing with industrial workplace accidents in Bangladesh by focusing on Rana Plaza tragedy in 2013. ILO plays an active role to promote decent work for every man and woman all over the world. Workplace accident is one of many problems usually found in garment industry in Bangladesh. Unsafe structural integrity and fire safety are the factors that cause workplace accidents.This research uses Pluralism Perspective and Role Concept. It also uses Organization theory and International Cooperation theory. These theories assume any cooperative arrangement instituted among states, usually by a basic agreement, to perform some mutually advantageous functions implemented trough periodic meetings and staff activities.In handling the workplace accidents in garment industry in Bangladesh, ILO cooperated with tripartite partners through joint statement and formulated an Action Plan as response to Rana Plaza tragedy. The joint statement was followed up by European Union and stake holders as a kind of responsibility to improve the working condition in garment industry in Bangladesh. ILO helped tripartite partners in implementing the Action Plan as solution to improve working conditions in garment industry after Rana Plaza tragedy with support from European Union and stakeholders. The cooperation between ILO (International Labour Organization), tripartite partner and stake holders has shown some improvements in working condition after Rana Plaza tragedy.Keywords : Action Plan, workplace accident, ILO, tripartite partner, cooperation